Exploring self-invertible 3×3 matrices for cipher trigraphic polyfunction with distinct encryption keys - Yunos, Faridah; Basri, Witriany; Asbullah, Muhammad Asyraf; Zulkifli, Ummu Zulaikha; Ibrahim, Syakirah (Universiti Putra Malaysia, 2024)
The encryption keys with self-invertible matrix in Hill Cipher cryptography and its extension, have been proven through various studies reducing the complexity of obtaining its inverse. Several methods to generate these keys have been applied to specific systems. This paper aims to find a submatrix id2 as a basis for generating self-invertible keys. Then, these keys are successfully implemented on a Cipher Trigraphic Polyfunction cryptosystem, which uses different encryption keys for each transformation.